2008
DOI: 10.1002/eji.200737578
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of antigen using a novel mannosylated dendrimer potentiates immunogenicity in vitro and in vivo

Abstract: Antigen mannosylation has been shown to be an effective approach to potentiate antigen immunogenicity, due to the enhanced antigen uptake and presentation by APC. To overcome disadvantages associated with conventional methods used to mannosylate antigens, we have developed a novel mannose-based antigen delivery system that utilizes a polyamidoamine (PAMAM) dendrimer. It is demonstrated that mannosylated dendrimer ovalbumin (MDO) is a potent immune inducer. With a strong binding avidity to DC, MDO potently indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 44 publications
(56 reference statements)
5
110
0
Order By: Relevance
“…MDO induces Ag presentation and DC maturation only in the presence of competent TLR4, while MDO internalization can be mediated by receptors including C-type lectins (18). MDO fails to elicit morphological/phenotypic maturation of C3H/HeJ DCs, in which no lysosomal localization is observed, given that it is bound and internalized at levels equivalent to wildtype C3H/He DCs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…MDO induces Ag presentation and DC maturation only in the presence of competent TLR4, while MDO internalization can be mediated by receptors including C-type lectins (18). MDO fails to elicit morphological/phenotypic maturation of C3H/HeJ DCs, in which no lysosomal localization is observed, given that it is bound and internalized at levels equivalent to wildtype C3H/He DCs.…”
Section: Discussionmentioning
confidence: 98%
“…Its immunogenicity was demonstrated by the strong OVA-specific immune responses induced in vitro and in vivo and by its efficacy in *Immunology and Vaccine Laboratory, Burnet Institute, Melbourne, Australia; induction of tumor protection in MDO-immunized mice (18). In the present study, using MDO as a PAMP-associated Ag, we further investigate its adjuvanticity in two heterogeneous DC populations, bone marrow DCs (BMDCs) composed of CD24 high and CD11b high subsets and fms-like tyrosine kinase 3 ligand (Flt3-L) DCs, which contain CD24 high , CD11b high , and B220 ϩ DCs (functional equivalents of mouse CD8 ϩ , CD8 Ϫ , and plasmacytoid subsets in vivo) (15,19).…”
Section: B220mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the number of end groups on the dendrimer doubles with each serial step. As well-characterized display systems of well-defined and controllable size, these materials have great potential as vaccine platforms 38 .…”
Section: Materials For Penetrating Tissue Barriersmentioning
confidence: 99%
“…In addition to protease resistance being beneficial for effective APL, an improvement in APL uptake can potentially reduce the need for APL overload. Antigen uptake by DC via the mannose receptor is improved by mannosylation of antigens [115][116][117], and Agnes et al demonstrated improved APL uptake and a 1000-fold selective increase in APL internalization into the endocytic compartments by generating bis-mannosylated APL [118].…”
Section: Generation Of Protease-resistant Aplmentioning
confidence: 99%